Environmental engineering design - Bùi Thị Thủy (Trường Đại học Thuỷ Lợi, 2021)
Contents: Chapter 1: Design and construction process; Chapter 2: General water supply design consideration; Chapter 3: Coagulation and flocculation facilities design; Chapter 4+5: Lime – soda softening and ion exchange; Chapter 7: Sedimentation; Chapter 8: Granular filtration; Chapter 9: Membranes; Chapter 10: Disinfection and fluoridation; Chapter 11: Water treatment plant residual management; Chapter 12 : General wastewater collection and treatment design considerations; Chapter 13: Headworks and preliminary treatment; Treatment design considerations